PENERAPAN MODEL PEMBELAJARAN PROBLEM POSING DALAM MENINGKATKAN HASIL BELAJAR PPKn KELAS X DI SMA SWASTA BINA KASIH KECAMATAN ARAMO - Seriman Ndruru (FAGURU: Jurnal Ilmiah Mahasiswa Keguruan, 2024)
The problem with this sentence is that it reduces students' learning motivation and leads to low learning outcomes. The purpose of this article is to determine the application of the problem learning model to improve PPKn learning. This letter uses the type of "class action lawsuit letter". The target audience for this paper is 26 students in class 73.85, and the completion rate is 100%. The conclusion of the letter is that the application of the problem learning model improves learning outcomes in Civics classes, and the author provides several suggestions: 1) Students should collaborate with other students in group discussions, need to get used to it and actively participate. Learning activities such as asking questions and expressing opinions can expand your information and knowledge. 2) Teachers should be more creative in maintaining students' learning motivation and should be more creative in implementing appropriate learning models so that learning is more effective and efficient. 3) Schools should improve the quality of learning and academic achievement by optimizing teacher performance through the implementation of innovative learning models. 4) Future authors should develop this text on a larger scale. Apart from that, other authors can further develop this text along with other variables that are more innovative and add insight to improve quality.